Gli2 acetylation at lysine 757 regulates hedgehog-dependent transcriptional output by preventing its promoter occupancy. - Sonia Coni; Laura Antonucci; Davide D'Amico; Laura Di Magno; Paola Infante; Enrico De Smaele; Giuseppe Giannini; Lucia Di Marcotullio; Isabella Screpanti; Alberto Gulino; Gianluca Canettieri (PLoS ONE, 2013)
The morphogenic Hedgehog (Hh) signaling regulates postnatal cerebellar development and its aberrant activation leads to medulloblastoma. The transcription factors Gli1 and Gli2 are the activators of Hh pathway and their function is finely controlled by different covalent modifications, such as phosphorylation and ubiquitination. We show here that Gli2 is endogenously acetylated and that this modification represents a key regulatory step for Hedgehog signaling. The histone acetyltransferase (HAT) coactivator p300, but not other HATs, acetylates Gli2 at the conserved lysine K757 thus inhibiting Hh target gene expression. By generating a specific anti acetyl-Gli2(Lys757) antisera we demonstrated that Gli2 acetylation is readily detectable at endogenous levels and is attenuated by Hh agonists. Moreover, Gli2 K757R mutant activity is higher than wild type Gli2 and is no longer enhanced by Hh agonists, indicating that acetylation represents an additional level of control for signal dependent activation. Consistently, in sections of developing mouse cerebella Gli2 acetylation correlates with the activation status of Hedgehog signaling. Mechanistically, acetylation at K757 prevents Gli2 entry into chromatin. Together, these data illustrate a novel mechanism of regulation of the Hh signaling whereby, in concert with Gli1, Gli2 acetylation functions as a key transcriptional checkpoint in the control of morphogen-dependent processes.